Interface entre o trabalho precoce e a prática de atos infracionais: uma análise de gênero - Almeida, Hana de Castro Dourado (2019)
The general objective of this dissertation is to analyze the relationship between early insertion at work and involvement in infractions based on gender analysis, based on hitorical cultural teory. Specific objectives: Identify boys and girls who carry out socio-educational measures in deprivation of liberty and have worked in childhood; Identify the ages at which boys and girls started working in childhood; To characterize the types of child labor that they performed in childhood and whether there is differentiation between genders; To characterize the context of involvement with the offending act of boys and girls; and Analyze the implications of the work performed by boys and girls for deviant socialization. To reach the objectives, diagnostic questionnaires were applied to identify the early workers and the ages in which they began to work. From this stage 23 boys and 13 girls participated in a socio-educational measure of deprivation of liberty in two socio-educational units in the city of João Pessoa. Once the early workers were identified, two discussion groups were held, one with four male adolescents and the other with seven female adolescents. The themes discussed were related to child labor, gender and infractions. Additionally, a questionnaire was applied to verify access to public health, education and social assistance. Data analysis was performed using the Thematic Content Analysis technique proposed by Minayo (2014) for the discussion groups and a descriptive analysis of data for the questionnaires. Most boys started working at age 10 in culturally recognized activities as male activities, such as in the construction industry, while the majority of girls started at age 13 in culturally-attributed women's activities such as housework and child care Access to health, education and social assistance programs and services did not provide the necessary elements for their withdrawal from situations of vulnerability and risk such as child labor, including the worst forms. Girls have an average of 2.5 years of school delay, boys have 4.7 years. The data show that there is a relation between having worked early and the infractions, a relation that does not happen in an equitable way between the genders. It is hoped that this dissertation may contribute to broadening the discussions about the relationship between child labor, infractions and the gender issues that pervade it.